Prescribing Cascades of Loop Diuretics and Anti-vertigo Drugs Following Treatment with Gabapentinoids and Benzodiazepines: Prescription Sequence Symmetry Analysis of a Large-Scale Claims Database Including Japanese Older Adults - Rina Omata; Akane Asami; Azusa Hara; Hisashi Urushihara (Adis, Springer Healthcare, 2024)
Abstract Background Gabapentinoids (GBP) and benzodiazepines (BZ) are commonly prescribed in older adults and their package inserts list edema and vertigo as adverse drug reactions. These adverse drug reactions may be treated with symptomatic drug therapies without discontinuing the culprit drugs or decreasing their dose, thereby initiating a prescribing cascade and often resulting in polypharmacy. Whether prescribing cascades occur in the treatment of edema and dizziness among Japanese patients treated with GBP and BZ has not been investigated, including treatment with mirogabalin, a class drug of GBP marketed in Japan. Objective We aimed to investigate prescribing cascades with GBP-induced and BZ-induced edema and dizziness treated with loop diuretics (LD) and anti-vertigo drugs (AVD), respectively, among older adults. Methods A prescription sequence symmetry analysis design was used to detect signals of prescribing cascades associated with edema and dizziness induced by GBP and BZ (exposure drugs). Loop diuretics and AVD were the outcome drugs used to identify prescribing cascades following the initiation of exposure drugs. The study population consisted of enrollees of a large-scale health claims database provided by DeSC Healthcare, Inc., between April 2014 and March 2021. Subjects eligible for a prescription sequence symmetry analysis were patients aged ≥ 65 years prescribed an outcome drug within 90 days before and after exposure drug initiation. A signal of a prescribing cascade was detected if secular trend-adjusted sequence ratios were statistically significant on comparison of the frequencies of outcome drug initiation before and after exposure drug initiation. Results We identified 2671 patients with prescriptions of a GBP-LD combination, 4009 with a GBP-AVD combination, 8675 with a BZ-LD combination, and 9462 with a BZ-AVD combination. The adjusted sequence ratios for GBP-LD and BZ-LD cascades were significantly larger than one (adjusted sequence ratio [95% confidence interval], 1.69 [1.56-1.83]; 1.35 [1.29-1.41], respectively), indicating positive signals of prescribing cascades. No signal was detected for the GBP-AVD or BZ-AVD cascade (0.89 [0.83-0.94]; 0.90 [0.87-0.94], respectively). The adjusted sequence ratio for the mirogabalin cascade was higher than that for pregabalin (2.23 [1.84-2.71] vs 1.59 [1.46-1.73]). Conclusions Our study provides good evidence that LD-prescribing cascades associated with edema would be a class effect of GBP and BZ. Edema emerging around 1 month after GBP initiation should be carefully differentiated from pathological edema, and undue LD prescription as a prescribing cascade should be avoided.